Merekonstruksi Pendidikan Karakter Melalui Peran Guru dan Orang Tua Terhadap Keberhasilan Belajar Siswa Disekolah - I Kadek Arta Jaya (UHN I Gusti Bagus Sugriwa Denpasar, 2021)
Education is a medium to educate the nation's life and bring this nation to the era of enlightenment. Education aims to build a sovereign nation order with the values of honesty, politeness, intelligence, sensitivity and concern for the life of the nation and state. Our education is experiencing a very sad character crisis. This very sad condition is still compounded by the decline in morality as happened to school children and the community. The decline in the morality of these children also occurred at SMK Negeri 5 Denpasar, where children were often late for school, during class hours there were still children outside the classroom playing in the canteen, sitting around chatting with friends, meeting teachers and other children. Children rarely greet or say hello to teachers at school. On the basis of this background, the title of this paper is reconstructing character education through the role of teachers and parents. By taking a discussion about how the school's partnership with parents, whether the influence of character education that is instilled from an early age can lead children to achieve success, and reconstruct character education through the concept of Tri Hita Karana. This study uses a qualitative method by using a literature study. Literature study is a document to complete the data obtained from observations and interviews. Where library research is a method that is carried out by exploring, observing, examining, and identifying existing knowledge in the literature (reading sources, reference books or other research results) to support research. Based on the results of the analysis carried out, it can be concluded that to achieve the success of education, it is necessary to have a school partnership with the family. Because with the partnership between the school and the family, the success of education will be achieved, because the family environment is the first educational environment, because it is in this family that children first receive education and guidance; The influence of character education will determine the success of students in school. In order to achieve the success of children's education in schools, it is necessary to instill the character of children such as: self- confidence; sociability; and the ability to communicate so that later our children will be able to build their own personality so that noble character will grow; and to form good children's characters, the concept of Tri Hita Karana's teachings is very appropriate to be developed in children from an early age in school which includes: characters related to the one and only God; character related to fellow human beings; and characters related to the environment.